Comparison of the WoS and Scopus Databases - Bülent Karasözen; Özlem Gökkurt Bayram; Burcu Umut Zan (Türk Kütüphaneciliği)
In this article, WoS and Scopus databases are being compared in terms of their content, subject headings and their regional comprehension. Also, the research are supported through an analysis of studies of the Social, Art and Humanities subjects which are published in the WoS and Scopus databases with Turkish address between 2000 - 2009 years. In the past decade, indexed studies, the incensement in the number of publishing, the subject headings which have presented the most increase were investigated.